Ecological footprints, global sustainability, and the roles of natural resources, financial development, and economic growth - Ali Hussein A. L. Marshadi; Muhammad Aslam; Azhar Ali Janjua (PLoS ONE, 2025)
The prevailing ecological deficit is devastating the ecosystem which is leading toward the unsustainability by endangering the livings on earth. The important drivers of this environment degradation are natural resources depletion, financial development and the economic growth which are investigated to test their impact on ecological footprints. The EKC hypothesis is evaluated to test the growth led environment pattern. This study incorporated twenty years (2002–2021) data of 146 countries and the group of countries are investigated into various quantiles, geographical regions and income wise groups formed by the World Bank. Keeping in view the heterogeneous data established through the Shapiro-Francia W test and graphical analysis, the panel quantile regression is used which is insensitive to heterogeneous data. Firstly, the impact of dependent variables is estimated on environment degradation using the 10th, 20th, 30th,40th, 50th, 60th, 70th, 80th, 90th and 99th quantiles. The results suggested that the natural resources depletion and financial development are deteriorating the ecological footprints, which varies from smaller in initial quantiles to large in later quantiles. NR in North America and FD in the Middle East & North Africa are severely deteriorating the environment quality. The economic growth is improving the ecology in East Asia and the Pacific. The negative impact of natural resources on environment degradation is found in all income groups albeit with varying intensities. The financial development in upper middle income and lower middle income groups is deteriorating the environment quality. The EKC hypothesis remained undetermined for the estimated quantiles and geographical regions whereas it is established in high income group only. The policy intervention is recommended to restrict the natural resources depletion and binding the credit facilities to invest in ecosystem friendly projects by curtailing the process of ecological deficit for global sustainability which may be initiated from the most environment degraded quantiles, geographical region and income group.